Risk factors for child stunting in Bangladesh: an analysis using MICS 2019 data - Tuhinur Rahman Chowdhury; Sayan Chakrabarty; Muntaha Rakib; Stephen Winn; Jason Bennie (BMC, 2022)
Abstract Background Malnutrition is considered a major public health challenge and is associated with a range of health issues, including childhood stunting. Stunting is a reliable and well-recognized indicator of chronic childhood malnutrition. The objective of this study is to determine the risk factors associated with stunting among 17,490 children below five years of age in Bangladesh. Methods Correlates of child stunting were examined using data generated by a cross-sectional cluster survey conducted in Bangladesh in 2019. The data includes a total of 17,490 children (aged < 5 years) from 64,400 households. Multiple logistic regressions were used to determine the risk factors associated with child stunting and severe stunting. Results The prevalence of stunting and severe stunting for children was 25.96% and 7.97%, respectively. Children aged 24 to < 36 months [Odds Ratio (OR) = 2.65, 95% CI: 2.30, 3.05] and aged 36 to < 48 months [OR = 2.33, 95% CI: 2.02, 2.69] had more risk of stunting compared to the children aged < 6 months. Children from Sylhet division had the greatest risk of stunting of all the eight divisions [OR = 1.26, 95% CI: 1.09, 1.46]. Children of secondary complete or higher educated mothers were less likely to develop stunting [OR = 0.66, 95% CI: 0.56, 0.79] compared with children of mothers having no education at all. Similarly, children of secondary complete or higher educated father [OR = 0.74, 95% CI: 0.63, 0.87] were found to have lower risk of stunting compared with children whose father hadn't any education. Substantially lower risk of stunting was observed among children whose mother and father both completed secondary education or above [OR = 0.59, 95% CI: 0.52, 0.69]. Children from the richest households [OR = 0.49, 95% CI: 0.41, 0.58] had 51% lower odds of stunting compared to children from the poorest households. Conclusions After controlling for socioeconomic and demographic factors, parental education and household position in the wealth index were found to be the most important determinants of child stunting in Bangladesh.